Advanced genome editing strategies for manipulation of plant specialized metabolites pertaining to biofortification - Bhambhani, Sweta; Kondhare, Kirtikumar R.; Giri, Ashok P. (Phytochemistry Reviews, 2022)
Emerging trends in molecular biology have progressed the knowledge of plant specialized metabolites with respect to diversity in structure, function and biosynthetic pathways. Being powerful genome-editing tools, Zinc Finger Nuclease, Transcription Activator-Like Effector Nuclease, and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) systems have found potential application in genome and epigenome engineering. CRISPR/Cas9 is being used for studying the functions of multiple genes and gene families in plants. Our analysis suggests that although a rapid progress has occurred for utilization of CRISPR/Cas9 tool in crop improvement, limited studies are available for its application in manipulation of gene clusters of useful specialized metabolites in plants. In this review, after describing briefly about the recent advancements in genome editing techniques, we have further discussed their applicability in the modulation of metabolite production and biofortification of food crops. We have also emphasized the importance of CRISPR/Cas9-based targeted deletion of larger chromosomal fragments or gene clusters towards value addition of crop plants. The current policies for CRISPR/Cas9-edited crop plants in different countries and their acceptability in market place is also discussed. We propose that advanced genome editing techniques, including a multiplex CRISPR/Cas9 system could serve as a versatile tool for rewiring of metabolite gene clusters and improving the levels of useful metabolites in plants.
Keywords: Cas9; Chromosomal fragment; CRISPR; Gene cluster; Genome editing; Plant specialized metabolites